A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from southern Vietnam - Nguyen, Sang Ngoc; Nguyen, Vu Dang Hoang; Nguyen, Luan Thanh; Murphy, Robert W. (Zootaxa, 2020)
A new skink of the genus Scincella Mittleman, 1950, from Binh Phuoc Province, southern Vietnam is described based on morphological data, including hemipenial characters, and nucleotide sequences from COI. The following morphological characters diagnose Scincella baraensis sp. nov.: relatively small size in adults (snout-vent length up to 49.2 mm); when limbs adpressed, toes do not or just reach fingers; 30 smooth midbody scale rows and dorsal scales not enlarged; 66–70 paravertebral scales; 64–66 ventral scale rows; 7 supralabials, the fifth and sixth below the center of the eye; enlarged temporal scales 1+2; nuchals present; ear with small auricular lobules; 18–20 smooth lamellae beneath toe IV; hemipenis smooth, short, and unforked; dorsum with faint black dots. The new species differs from its congeners by an uncorrected p-distance in COI sequences of at least 16.2%.